Aggressive intramuscular hemangiomas in the upper extremity: A case report. Issue 3 (January 2017) - Lu, Hui; Chen, Qiang; Yang, Hu; Shen, Hui
Abstract: Introduction: Intramuscular hemangioma (IMH) is a rare congenital soft tissue tumor. Here, we report a case of IMH patient who had undergone several surgeries and other treatments that were all ineffective before he visited us. Clinical Findings: This IMH patient was a 16-yearold male who was born with a tumor of unknown size in his right hand and forearm. On physical examination, the tumor and skin flap complex was seen with a size of 14 cm_12 cm in his right hand, and the multiple postoperative scars were shown on his right hand and forearm. The patient was not able to raise his right shoulder, and the ranges of motion of his right elbow, wrist, and finger were almost zero degrees. Interventions: Considering that the tumor had been surgically excised for several times and the multiple recurrences had affected adversely his daily life, an amputation of his right hand, forearm, and the part of his right arm was performed. Diagnoses: The pathological examination confirmed the diagnosis of IMH. Outcomes: After the amputation surgery, the patient gained a functional recovery and the tumor did not recur during the 2 years after the surgery. Conclusion: A treatment of choice should be personalized according to an IMH patient's overall situation. For an IMH patient like our case with a history of multiple tumor recurrences, we suggest that an amputation surgery should be performed as early as possible to avoid the repeated, but ineffective surgical excisions and the unnecessary sufferings.